Adsorption Potential Distributions for Silicas and Organosilicas - Jerzy Choma; Mietek Jaroniec (Adsorption Science & Technology)
Adsorption potential distributions (APDs) were calculated from nitrogen adsorption isotherms for macroporous silicas, and for disordered and ordered mesoporous silicas without and with organic groups attached to the surface. It was shown that the APDs for porous silicas and organosilicas differ significantly from those obtained for carbonaceous materials, especially in the range of high adsorption potentials which correspond to low relative pressures. Although the high adsorption potential portions of APDs for porous siliceous materials are less informative than those for carbons, they are still useful for monitoring the changes in the surface properties due to the attachment of various organic groups.